Thin-walled flexible concrete pipes with synthetic fibers and reduced traditional steel cage. (1st October 2015) - Park, Yeonho; Abolmaali, Ali; Beakley, Josh; Attiogbe, Emmanuel
Highlights: An increase in fibers results in an increase in pipe stiffness of thin wall pipes. The radial tension limit states in thin wall pipes are improved by synthetic fibers. Inclusion of fibers doubled pipe stiffness over that of TW pipes without fibers. The addition of synthetic fiber is more effective in large diameter thin wall pipes. Abstract: Structural classification of buried pipes depends on their inherent response to external loading and interaction between the pipes and the surrounding soil. There are mainly two classified types of pipes, rigid pipes and flexible pipes. This study focused on performance evaluations of a proposed new class of concrete pipes, semi-rigid pipes, which are flexible concrete pipes that are reinforced with synthetic fibers and have thinner walls relative to standard concrete pipes. The innovative flexible concrete pipe system has the advantages of simplified structural design, thinner pipe walls, lighter weight, improved durability due to the use of non-corrosive reinforcement (synthetic fibers), and potentially lower production cost due to reduction of steel reinforcement and wall thickness. Based on the three-edge bearing test in accordance with ASTM standard C497, 44 thin walled concrete pipes (flexible concrete pipes) with diameters from 760 mm (30 in.) to 3050 mm (120 in.) were tested with different fiber dosages (ranges of 1.2–14.3 kg/m 3 ) and reduced steel reinforcement (ranges of 35–50% reduction). Test results show that discrete synthetic fibers increase the shear capacity of the thin walled concrete pipes and delay the shear failure mode, significantly enhancing the load carrying capacity with the reduced steel reinforcement. Moreover, thin walled concrete pipes with 50% reduction of steel reinforcement and the addition of synthetic fibers maintained bending stiffness up to 5% deflection of the inside diameter for small diameter pipes [760 mm (30 in.), 910 mm (36 in.) and 1370 mm (54 in.)], and bending stiffness up to 3% deflection for large diameter pipes [1830 mm (72 in.), 2130 mm (84 in.) and 3050 mm (120 in.)].